1993
DOI: 10.1007/bf00171889
|View full text |Cite
|
Sign up to set email alerts
|

The presence, nature, and role of gut microflora in aquatic invertebrates: A synthesis

Abstract: This review of the literature concerns the gut microbiota of aquatic invertebrates and highlights the questions and processes that merit attention if an understanding of the role of gut microbes in the physiology of host invertebrates and nutrient dynamics of aquatic systems is to be gained. A substantial number of studies report the presence of gut microbes in aquatic invertebrates. Crustacea, Mollusca, and Echinodermata have received the most attention, with few studies involving other invertebrate groups. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
289
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(305 citation statements)
references
References 165 publications
(356 reference statements)
12
289
3
1
Order By: Relevance
“…This overall pattern was also evident when the rate of nitrous oxide emission was expressed per milligram dry weight of the specimens (Table S1). Because FD-feeding species ingest greater numbers of microbes than predators do (10), this observation suggests microbial nitrogen conversions in the gut of the invertebrates as the source of nitrous oxide. Given anoxic conditions and the availability of easily degradable organic carbon in the gut of terrestrial and aquatic invertebrates (8,11), we hypothesized that nitrous oxide production was due to the activity of denitrifying bacteria in the animal gut.…”
Section: Resultsmentioning
confidence: 98%
“…This overall pattern was also evident when the rate of nitrous oxide emission was expressed per milligram dry weight of the specimens (Table S1). Because FD-feeding species ingest greater numbers of microbes than predators do (10), this observation suggests microbial nitrogen conversions in the gut of the invertebrates as the source of nitrous oxide. Given anoxic conditions and the availability of easily degradable organic carbon in the gut of terrestrial and aquatic invertebrates (8,11), we hypothesized that nitrous oxide production was due to the activity of denitrifying bacteria in the animal gut.…”
Section: Resultsmentioning
confidence: 98%
“…The influence of the gut flora on the host is clearly of great interest in aquaculture, particularly where poor productivity and stock losses are widespread (Ravichandran and Kannupandi, 2005). Within aquatic and other marine animals, the colonization of the digestive system by microorganisms is influenced by a number of both host-related and non host-related factors (Harris, 1993). In the gut of another freshwater culture animal, the Chinese mitten crab, investigation illustrated that Proteobacteria and Bacteroidetes might be the dominant population .…”
Section: Discussionmentioning
confidence: 99%
“…Differcording to the environmental condition. It was reported that intestinal flora of invertebrates was important to digest cellulose (Harris 1993). Acartia spinicauda could digest cellulose more efficiently with the flora suitable for the cellulose degradation in each habitat.…”
Section: -4 Cellulase Activities In the Temperate Climate Wetlandsmentioning
confidence: 99%